Identification of muscle activities involved in hyoid bone movement during swallowing using computer simulation - Kikuchi, Takahiro; Michiwaki, Yukihiro; Azegami, Hideyuki (Computer methods in biomechanics and biomedical engineering., 2023)
It is difficult to clarify the activity of swallowing-related muscles and the movement of organs. To represent the relationship between muscle activity and organ movement, a numerical simulator that reflects muscle contraction is necessary. However, no continuum organ models can identify and reflect muscle activity. In this study, a novel method was developed for obtaining the time change in the activities of all muscles involved in hyoid excursion. An organ model was developed based on four-dimensional computed tomography (4DCT) images acquired using a 320-column area detector CT, and the organ movement was analysed using a particle method. To identify the muscle activity, an evaluation function was defined and calculated considering the errors of velocities and positions of the hyoid bone, and the muscle activities to minimise the evaluation function were calculated using gradient descent. The results showed that the hyoid movement represented by the simulation model and the objective movement obtained from 4DCT images were in good agreement. The identified muscle activities were discussed through a comparison with the literature on electromyography measurements and the results of simulations using other methods. The proposed continuum organ model with muscles was considered able to clarify both muscle activity and organ movement.